2020
DOI: 10.1039/d0qi01023e
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide dioxygenation (NOD) reactions of CoIII-peroxo and NiIII-peroxo complexes: NODversusNO activation

Abstract: Here, we report the nitric oxide dioxygenation (NOD) reactions of NiIII-peroxo, [(12-TMC)NiIII(O22−)]+ (NiIII-O22−, 1), and CoIII-peroxo, [(12-TMC)CoIII(O22−)]+ (CoIII-O22−, 2), complexes bearing N-tetramethylated cyclam (TMC) ligands. The reaction of complex 1...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 103 publications
0
19
0
Order By: Relevance
“…3a and 6a). 19 d ,20 b ,21 a ,27,30,32 Astonishingly, 2 upon reaction with VCl 3 generated corresponding Co III -nitrosyl complex 4, ({CoNO} 8 ), 19 d ,20 b ,21 a ,27,30 with V V -Oxo species in both aqueous/or methanol medium at 298 K ( Scheme 1 ; reaction II). It is important to note that 2 did not show any spectral changes in the absence of VCl 3 , suggesting that 2 is highly stable in H 2 O/or MeOH and at 298 K (ESI, ES, and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a and 6a). 19 d ,20 b ,21 a ,27,30,32 Astonishingly, 2 upon reaction with VCl 3 generated corresponding Co III -nitrosyl complex 4, ({CoNO} 8 ), 19 d ,20 b ,21 a ,27,30 with V V -Oxo species in both aqueous/or methanol medium at 298 K ( Scheme 1 ; reaction II). It is important to note that 2 did not show any spectral changes in the absence of VCl 3 , suggesting that 2 is highly stable in H 2 O/or MeOH and at 298 K (ESI, ES, and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of NO overproduction, nitric oxide dioxygenase (NODs) generates NO 3 − in the reaction of the iron–dioxygen adduct with NO via a proposed PN intermediate, 19 as explored in other biomimetic systems. 19 d ,20 Also, there are various reports on NO 2 − formation in nitric oxide monooxygenation (NOM) reaction from metal-nitrosyls in the presence of O 2 , O 2 ˙ − and OH − .…”
Section: Introductionmentioning
confidence: 99%
“…We found that all ions adopt a side-on (η 2 ) mononuclear cobalt(III)-peroxo geometry in analogy with other structures reported in literature (Figure 2). [9][10][11][12][13] Moreover, this side-on O2 ligand adopts a distorted axial geometry which puts all the amino groups within the common natural hydrogen bonding distance (2.7 to 3.3 Å) of the axial oxygen atom (Table S2 in the Supporting Information). 14 Hydrogen bonding leads to a red shift of the N-H stretch to lower wavenumbers and the shift correlated with the bond strength of the hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above experimental results and their interpretations, labile & inert nature of more stable 6-CrNO (low spin d 5 , S = ½, inert) (Figure S15a) and less stable 5-Cr (high spin d 4 , S = 2, labile) (Figure S15b) suggests a huge change in the spin state which promotes the reaction to move in the forward direction. [37][38] The above discussion suggests that the ligand frameworks may influence the intermediate's stability and the rate of NO transfer; however, when it comes to the net transfer of coordinated NO moiety from one metal to another, it largely depends upon the stability of the metalcenter and various other physical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…S15b †) suggests a huge change in the spin state, which promotes the reaction to move in the forward direction. 37,38 The above discussion suggests that the ligand frameworks may inuence the intermediate's stability and the rate of NO transfer; however, when it comes to the net transfer of coordinated NO moiety from one metal to another, it largely depends upon the stability of the metalcenter and various other physical parameters.…”
Section: Discussionmentioning
confidence: 99%